2021
DOI: 10.1055/a-1673-5546
|View full text |Cite
|
Sign up to set email alerts
|

Countering COVID-19 Vaccine Hesitancy in Pregnancy: the “4 Cs”

Abstract: Despite evidence to support the safety and efficacy of COVID-19 vaccination in pregnancy, and clear recommendations from professional organizations and the CDC for pregnant people to get vaccinated, COVID-19 vaccine hesitancy in pregnancy remains a significant public health problem. The emergence of the highly transmissible B.1.617.2 (Delta) variant among primarily unvaccinated people has exposed the cost of vaccine hesitancy. In this commentary, we explore factors contributing to COVID-19 vaccine hesitancy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
40
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 51 publications
2
40
0
1
Order By: Relevance
“…in utero worldwide could reach up to 20 million per year, particularly in the setting of low COVID-19 vaccine uptake in pregnant populations [23,24]. In fact, a 12-month follow-up of more than 7000 deliveries in a large hospital system, including more than 200 COVID-19-exposed pregnancies, suggested that prenatal SARS-CoV-2 infection is associated with an increased risk for offspring neurodevelopmental diagnoses [25].…”
Section: Highlightsmentioning
confidence: 99%
“…in utero worldwide could reach up to 20 million per year, particularly in the setting of low COVID-19 vaccine uptake in pregnant populations [23,24]. In fact, a 12-month follow-up of more than 7000 deliveries in a large hospital system, including more than 200 COVID-19-exposed pregnancies, suggested that prenatal SARS-CoV-2 infection is associated with an increased risk for offspring neurodevelopmental diagnoses [25].…”
Section: Highlightsmentioning
confidence: 99%
“…Compounded by their exclusion, there is considerable vaccine hesitancy amongst pregnant women. 2 Such hesitancy persists, even though at present adverse outcomes of SARS-CoV-2 infection are increasing among pregnant and postpartum women in many countries, 3 while these are improving in most other groups. The impact of the omicron variant is, as yet, unknown.…”
mentioning
confidence: 99%
“…Lack of confidence about the safety of the vaccine in pregnancy as well as concern for potential risks to the fetus are the most common reasons for vaccine hesitancy in reproductive-aged women. 2 The decision to exclude pregnant and lactating individuals from early COVID-19 vaccine clinical trials has confirmed what we knew all along—the absence of medical information can be just as harmful as misinformation.…”
mentioning
confidence: 84%